Paleoenvironmental reconstruction of Late Cretaceous rivers, Dinosaur Park Formation, Alberta, Canada - Mayo, Katrina; Silva, Ricardo L.; Durkin, Paul R. (Sedimentary geology, 2023)
Dinosaur Provincial Park is a UNESCO World Heritage Site with one of the richest vertebrate fossil accumulations globally. The “badlands”-style topography exposes Upper Cretaceous (Campanian) meander-belt deposits of the Dinosaur Park Formation, providing an excellent opportunity for sedimentological and three-dimensional stratigraphic analysis. One of the main unknowns regarding the depositional environments of the Dinosaur Park Formation, specifically the proximity to the fluvial-to-marine transition zone, has been the subject of extensive debate. Our study aims to refine paleoenvironmental reconstructions of Late Cretaceous rivers through facies and facies associations analysis, meander-belt architecture characterization, and paleohydraulic parameter calculations. We investigate a ~7 m thick single-story meander-belt interval of the Dinosaur Park Formation. Six facies, four facies associations, and two architectural elements (both point bars) were identified from 20 stratigraphic sections. In addition, paleohydraulic reconstruction of the formative river channel was completed by estimating bankfull channel depth and width, paleoslope, and backwater length. Contrasting with previous interpretations of deposition (partially or wholly) influenced by tides, these data allow us to demonstrate that the meander-belt deposits of the Dinosaur Park Formation were deposited in a fluvial environment upstream of the fluvial–marine transition zone. Inclined heterolithic strata (IHS) present in the area are of fluvial origin, adding to the growing body of evidence for heterolithic bedding in fluvial point-bar environments. The newly inferred depositional setting for the studied portion of the Dinosaur Park Formation changes our understanding of the paleogeography of the Western Interior Seaway in western Canada and will allow paleontologists to revise the reconstructions of dinosaur habitats and better constrain the taphonomy of these globally significant fossil accumulations. Additionally, this study contributes to the validation and development of a systematic approach to the paleoenvironmental reconstruction of ancient river systems based on paleohydraulic analysis.